Box-Behnken Design of Chitosan-NPs Encapsulating 5-Fluorouracil and Santalum album Essential Oil and Investigating their Combinatorial Therapeutic Effect against Triple Negative Breast Cancer (TNBC) cell line. - Tawfik, Somaia (AUC Knowledge Fountain, 2025)
Despite its widespread use, the clinical utility of 5-fluorouracil (5FU) is limited by systemic toxicity, poor selectivity, and drug resistance in aggressive cancers, such as the Triple Negative Breast Cancer (TNBC). This study investigates a polymeric hybrid nanoparticle (NP) system co-delivering 5FU with Santalum album EO (SAEO), a natural product rich in α- santalol, to enhance therapeutic efficacy and achieve controlled release for TNBC Treatment. Chitosan-based nanoparticles were developed using ionic gelation to encapsulate 5FU and SAEO, followed by the Design of Experiments (DOE) optimization. The optimized nanoparticles exhibited a mean size of 363.8 ± 11.68 nm, a zeta potential (ZP) of 12.7 ± 0.57 mV, and demonstrated a high encapsulation efficiency (EE%) of 88.60 ± 0.73.% along with a loading capacity (LC%) of 17.0 ± 0.08%. Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA) confirmed successfully incorporating 5- 5FU and SAEO into the system. The nanoparticles displayed controlled and sustained drug release characteristics compared to free 5FU. The combinatorial formulation of 5FU/SAEO@CS-NP exhibited superior anti-cancer activity, with IC50 values recorded at 12.1 ± 0.20 μg/mL for MDA-MB-231 cells and 8.7 ± 1.43 μg/mL for MCF-7 cells. The free SAEO and SAEO@CS-NP formulations demonstrated significant selectivity toward the MDA-MB-231 cells, and at the prospective IC50, normal cells are viable by more than 80%.